2014
DOI: 10.1107/s2053230x14002052
|View full text |Cite
|
Sign up to set email alerts
|

The 2.2 Å resolution structure of the catalase-peroxidase KatG fromSynechococcus elongatusPCC7942

Abstract: The crystal structure of catalase-peroxidase from Synechococcus elongatus PCC7942 (SeKatG) was solved by molecular replacement and refined to an Rwork of 16.8% and an Rfree of 20.6% at 2.2 Å resolution. The asymmetric unit consisted of only one subunit of the catalase-peroxidase molecule, including a protoporphyrin IX haem moiety and two sodium ions. A typical KatG covalent adduct was formed, Met248-Tyr222-Trp94, which is a key structural element for catalase activity. The crystallographic equivalent subunit w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Although the electron density for Se KatG was mostly continuous and of high quality, the densities for the N‐terminal segment (residues 1–10) were poorly defined; accordingly, these residues were not included in the model. When the structure of INH‐bound Se KatG was superposed on that of substrate‐free Se KatG , no significant structural changes were observed in the enzyme; the rmsd for the C α atoms was 0.15 Å.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Although the electron density for Se KatG was mostly continuous and of high quality, the densities for the N‐terminal segment (residues 1–10) were poorly defined; accordingly, these residues were not included in the model. When the structure of INH‐bound Se KatG was superposed on that of substrate‐free Se KatG , no significant structural changes were observed in the enzyme; the rmsd for the C α atoms was 0.15 Å.…”
Section: Resultsmentioning
confidence: 98%
“…Crystals of INH‐bound Se KatG were nearly isomorphous with those of native KatG, and the structure of INH‐bound Se KatG was determined with the structure of native KatG (Protein Data Bank ID: http://www.rcsb.org/pdb/search/structidSearch.do?structureId=3WNU) as a model . The structure was subjected to rigid‐body refinement from 25‐Å to 3.0‐Å resolution with refmac 5 from the ccp 4 package .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the INH‐free wild‐type Se KatG (Fig. 2B) [17] and INH‐bound wild‐type Se KatG (Fig. 2C) [14], the map around the heme propionate moiety clearly showed that water molecules occupied in this space.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms of INH activation have been explored not only in M. tuberculosis KatG (MtKatG) [5][6][7] but also in other KatGs such as those of Burkholderia pseudomallei (BpKatG) [4,[8][9][10], Synechocytis PCC 6803 (SynKatG) [11][12][13] and Synechococcus elongatus PCC7942 (SeKatG) [14]. These KatGs share at least 54% sequence identity, and their overall structures are very similar [15][16][17]. In addition, the configuration of the residues around the heme, including the unique covalent bonds among the side chains of the Met-Tyr-Trp residues of KatG, located on the distal side of the heme, are found in KatG proteins from all three species.…”
Section: Introductionmentioning
confidence: 99%